Design of Gaussian basis sets to the theoretical interpretation of IR-spectrum of hexaaquachromium (III) ion, tetraoxochromium (IV) ion, and tetraoxochromium (VI) ion - Savedra, RML; de Lima, KCV; Pinheiro, J. C.; Kondo, R. T.; Treu, O.; Davolos, Marian Rosaly [UNESP]; Jafelicci, M.; Martines, MAU (Elsevier B.V., 2003)
The Generator Coordinate Hartree-Fock (GCHF) method is employed to design 16s, 16s10p, 24s17p13d, 25s17p13d, and 26s17p Gaussian basis sets for the H ((2)S), O ((3)P), O(2-) ((1)S), Cr(3+) ((4)F), Cr(4+) ((3)F), and Cr(6+) ((1)S) atomic species. These basis sets are then contracted to (4s) for H ((2)S), (6s4p) for O ((3)P), and O(2-) ((1)S), (986p3d) for Cr(3+) ((4)F), (10s8p3d) for Cr(4+) ((3)F), and (13s7p) for Cr(6+) (1S) by a standard procedure. For evaluation of the quality of those basis sets in molecular calculations, we have accomplished studies of total and orbital (HOMO and HOMO-1) energies at the HF-Roothaan level for the molecular species of our interest. The results obtained with the contracted basis sets are compared to the values obtained with our extended basis sets and to the standard 6-311G basis set from literature. Finally, the contracted basis sets are enriched with polarization function and then utilized in the theoretical interpretation of IR-spectrum of hexaaquachromium (III) ion, [Cr(H(2)O)(6)](3+), tetraoxochromium (IV) ion, [CrO(4)](4-), and tetraoxochromium (VI) ion, [CrO(4)](2-). The respective theoretical harmonic frequencies and IR-intensities were computed at the density functional theory (DFT) level. In the DFT calculations we employed the Becke's 1988 functional using the LYP correlation functional. The comparison between the results obtained and the corresponding experimental values indicates a very good description of the IR-spectra of the molecular ions studied, and that the GCHF method is still a legitimate alternative for selection of Gaussian basis sets. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: design of basis sets; contracted basis sets; hexaaquachromium (HI) ion; tetraoxochromium (IV) ion; tetraoxochromium (VI) ion